IMPLEMENTATION OF JUDICIAL ACTIVISM IN JUDGE’S DECISION - Indriati Amarini (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2019)
The task of the judge in realizing justice is inseparable from the decisions that are made. A qualified judge's decision is obtained through the judge's thought process through a choice of judges that reflects judicial activism. The problem in this research is how judicial activism is used by judges in issuing decisions and how the implementation of judicial activism in decision making. Judicial Activism is the choice of decision making by judges in order to realize justice. Judicial activism in the Indonesian judicial system is regulated in Article 5 paragraph (1) of Law Number 48 of 2009 concerning Judicial Power. The law requires judges to explore the law and sense of justice that lives in society. The implementation of judicial activism is carried out by judges through means of legal discovery. Through means of legal discovery, judges play an active role in realizing justice as a law that lives in a dynamically developing society.